EFFECTIVENESS OF SELF-SCREENING INSTRUMENT IN ASSESSING THE CONDITION OF PARTICIPANTS IN OUTDOOR ACTIVITIES - Endang Sepdanius; Anton Komaini; Muhammad Sezelirifki (The Tourism, Heritage and Recreation Sport Center, Universitas Negeri Padang, 2019)
Special attention is given to participants in outdoor activities to remain safe. Preparation is the main thing to keep our health physically and psychologically. Therefore we need an instrument to assess personal health condition easily and precisely. The results obtained are used to make a decision to continue the activity or consult with the doctor first before doing the activities. The aim of this research is to see the effectiveness the self-screening instrument that developed. This research did in three step as: (1) preliminary study phase, (2) Expert validation phase, (3) testing phase. The number of participant that contributed in this research were 826 participants consist of three expert, 100 participants in small scale test and 723 participants in large scale test. The result of expert’s judgment showed that self-screening instrument has content validity. The result of small-scale test showed that 19 questions were valid and in large-scale test, information was obtained in a short time about the condition of the participants, that 97.1% of the total participants who did not have problems. While 2.9% of the total participants has problems that needed consultation and recommendations from doctors. Based on these results, it can be seen that effectiveness of self screening instrument in screening participants quickly and precisely so that they can prevent the occurrence of problems related to the situation of participants.